Antioxidant Activity of Peel-off Mask from Pangasius Catfish Gelatin (Pangasius hypophthalmus) with Astaxanthin - Yus Nasution, Azlaini; Sari, Novia Novita; Fauzana, Annisa (Pharmacon: Jurnal Farmasi Indonesia, 2024)
Peel-off face masks are a type of mask that contains elastic materials such as gelatin, making them easy to apply and remove. These peel-off masks are applied to the face by spreading them to form a thin, transparent film layer. Pangasius catfish gelatin serves as the gelling agent in the formulation of the peel-off mask, and astaxanthin is added as an antioxidant. Astaxanthin is a carotenoid pigment with a molecular structure similar to β-carotene, exhibiting stronger antioxidant activity compared to β-carotene in neutralizing free radicals. The purpose of this research is to determine the antioxidant activity of peel-off gel masks made from pangasius catfish (Pangasius hypophthalmus) gelatin supplemented with astaxanthin using the DPPH method. Astaxanthin extract was used as the active ingredient in the production of the peel-off gel mask, with an astaxanthin extract concentration of 0.5%. The results of the antioxidant activity test for the peel-off gel mask made from pangasius catfish gelatin supplemented with astaxanthin yielded an IC50 value of 7572.84 µg/mL, while the IC50 value for the comparative mask (Brightening lemon blackhead brand) was 5045.74 µg/mL. These results indicate that the mask produced has lower antioxidant activity compared to the comparative masks available in the market.